Unilateral Open-Angle Glaucoma Associated with the Ipsilateral Nevus of Ota - Lidija Magarasevic; Zihret Abazi (Case Reports in Ophthalmological Medicine)
The nevus of Ota also known as “congenital melanosis bulbi” and “oculodermal melanocytosis” is a blue-gray hyperpigmentation that occurs on the face and eyes. The sclera is involved in two-thirds of cases (causing an increased risk of glaucoma). Women are nearly five times more likely to be affected than men. It is rare among Caucasian people. The nevus of Ota is congenital or acquired. Most cases of the nevus of Ota are unilateral (90%), although pigmentation is present bilaterally in 5%–10%. Ocular abnormalities included pigmentation of the sclera, cornea, retina, and optic disc and cavernous hemangiomas of the optic disc, elevated intraocular pressure, glaucoma, and ocular melanoma. We reported an appearance of unilateral glaucoma in a Caucasian female patient with the acquired, ipsilateral nevus of Ota.